Diversity and distribution of elasmobranchs in the coastal waters of Cyprus: using bycatch data to inform management and conservation - O’Keefe, Martha; Bengil, Elizabeth G. T.; Palmer, Josie L.; Beton, Damla; Çağlar, Çiğdem; Godley, Brendan J.; Özkan, Meryem; Snape, Robin T. E.; Broderick, Annette C. (Frontiers in Marine Science, 2023)
Introduction Loss of biodiversity in marine ecosystems is a globally acknowledged problem. To address this and avoid extinctions, improved conservation is required to protect and restore our oceans. Elasmobranch species are considered the second most threatened vertebrate lineage, with overfishing considered the most important driver of declines. The Mediterranean Sea is a hotspot for elasmobranchs, with the eastern basin considered a data-poor area. Methods This study sought to address that deficiency, using bycatch data to assess the diversity and distribution of elasmobranch species caught as a result of commercial fishing in Northern Cyprus from 2018 to 2022. Results Thirty-six elasmobranch species were recorded, including 24 new records for Northern Cyprus, representing 41% of all species recorded in the Mediterranean. Of these 36 species, 61% are listed on the IUCN Red List as globally threatened (Critically Endangered, Endangered or Vulnerable). Of the species recorded, 71% of sharks (n=17), and 53% of batoids (skates and rays; n=19) are listed as threatened. We present data on the distribution of captures and size classes and infer life stage from these data. Discussion Our study demonstrates the importance of the coastal waters of Cyprus for multiple life stages of a broad range of elasmobranch species. As most elasmobranchs caught are retained for bait, subsistence or trade, our study has highlighted the need to update the regulations for this small-scale fishery, and led to a recent amendment to prohibit trade in all species listed under the Barcelona Convention.